Limb Amputation - Fujioka, Masaki (IntechOpen, 2020)
Patients often need to have limbs amputated to save them from advanced malignant neoplasms and severe limb infections, or due to the failure to repair severe limb trauma. However, efforts should be made to maintain limbs where possible, and to minimize loss of function if amputation is required. We provide the latest developments in limb amputation for this purpose. This book provides expert commentary on the following issues: cutting to prevent large-scale amputations in peripheral arterial disease and diabetes, optimal wound treatment in severe trauma, troubles of prostheses due to stump overgrowth in amputation in children.We hope this book will help physicians dealing with limb illness and trauma, and all amputee patients.